The Money Multiplier in The Modern Financial Systems ("Journal "U". Economy. Management. Finance.", 2020)
The article considers the mechanism of action of the money multiplier and its role in the formation of economic policy by Central banks.
Keywords: money multiplier; money supply; money base; money aggregate; Central Bank; monetary policy